Semiotic Analysis of the Movie ‘Super Deluxe’ (2019) - Amalan G, Jeaya (Journal of Advanced Research in Journalism & Mass Communication, 2023)
The goal of storytelling in contemporary film is to create stunning visual displays of colour, settings, clothing, other elements. Most of the time, these few props, outfits, or locations can have deeper connotations or serve as ‘symbols’. The study of semiotics focuses on the meaning that words and other symbolic systems of communication convey. With a better knowledge of semiotics, modern film has progressed beyond just narrating stories to using mise-en-scene to give the narrative symbolic significance. Hyperlink cinema is a multilinear form of cinema involving interwoven storylines, plot twists, flashback and flash-forward sequences. Alissa Quart (2005). In the year 2019, Thiagarajan Kumararaja directed the Tamil film “Super Deluxe.” A hyperlink non-linear narrative structured film. This movie have four different plots which are interconnected to each other. Qualitative research method is used in this study. Researcher used Ferdinand de Saussure’s theory of semiotics in mise-en-scene of the movie as signifier and what is signified through it to understand the hyperlink non-linear narration of the film. How to cite this article: Amalan GJ. Semiotic Analysis on the Movie ‘Super Deluxe’ (2019). J Adv Res Jrnl Mass Comm 2023; 10(1): 13-17. DOI: https://doi.org/10.24321/2395.3810.202303